Determinant of Affective Commitment: Mediation and Moderation Mechanism of Job Satisfaction and Job Tenure - Noermijati, Noermijati; Tri Kurniawati, Desi; Farhiya, Daniyatul; Masyhuri, Masyhuri (MIX: JURNAL ILMIAH MANAJEMEN, 2024)
Objectives: The objective of this study is to analyze the effect of followership in increasing affective commitment, complemented by a mediation mechanism using job satisfaction and moderating variable job tenure.Methodology: This study is using the quantitative research approach involving 131 employees from the service industry in East Java. Data retrieval using a convenience sampling technique. The instrument used is a questionnaire that is distributed online. Data analysis used SEM_PLS with Smartpls 3.0 application. Finding: The results found that followership can increase work satisfaction, and job satisfaction can directly affect commitment. Surprisingly, good followership had no direct effect on affective commitment. However, the followership mediation mechanism successfully increases affective commitment through job satisfaction. Finally, job tenure has succeeded in strengthening the role of followership in increasing affective commitment.Conclusion: These findings suggest that if a leader wants to increase employees' affective commitment using a followership attitude, they must pay attention to employee job satisfaction and tenure.